Technological and knowledge development of dairy farms in the South of Minas Gerais State - Bassotto, Leandro Carvalho; Putti, Fernando Ferrari [UNESP]; de Benedicto, Gideon Carvalho (Centro Universitario de Maringa, 2024)
Dairy farming is an important sector of agribusiness responsible for generating wealth and income for farmers of different sizes. Therefore, it is necessary to characterize the dairy properties to identify the level of technological development and knowledge of the sector. The aim of the study was to diagnose the level of knowledge of milk producers in the southern region of the state of Minas Gerais about the degree of technological development in the sector. The research is characterized by being descriptive with a quantitative approach, in which 112 milk producers from eight cities in the south of the state of Minas Gerais were interviewed. Therefore, we used the data analysis technique called cluster analysis, which allowed the formation of four groups of properties. It identified that, although there are producers with high knowledge and properties with high technological advances, small farms with a low degree of technological development and producers with little concern for the importance of knowledge for the development of the dairy activity predominate. It is concluded that the degree of technological development of dairy farms in the south of Minas Gerais is low, a condition that may expose properties to risks of continuity and/or development.
Desenvolvimento tecnológico e do conhecimento de propriedades leiteiras do Sul de Minas Gerais
Keywords: Dairy livestock; Production resources; Production technologies